PELAKSANAAN HAK KESELAMATAN DAN KESEHATAN KERJA KARYAWAN PABRIK KELAPA SAWIT PT. PERKEBUNAN NUSANTARA V SEI GARO DI KABUPATEN KAMPAR BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Arif Chandra Saragih; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Workers are the sole responsibility of the company. Entrepreneurs are people who run the company, which is managing the company, better manage yourself, manage or through another person or the help of others, and employers may be an individual or legal entity. Safety is a program created for the workers / laborers and employers in an effort to prevent the occurrence of occupational accidents and diseases caused by working relations in the work environment by identifying the things that potentially cause accidents. The high number of accidents showed adequate management of the company in the implementation of the safety and health of workers. So, to reduce the number of accidents, it is considered very necessary to have legal protection against any employee or employment under the legislation. Especially employees working in the factory and factory workers who work at night are certainly at risk of work accidents is higher and nutrient intake or pudding is better than the employees who work in the office and other field.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at PT. Perkebunan Nusantara V Sei Garo Kampar, while the sample population is a whole party with regard to the problems examined, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews and literature study.From the research of this problem has three main things that can be inferred. First, the implementation of occupational safety and health of employees mills in PT. Perkebunan Nusantara V Sei Garo has not done well and have not been efficient. Second, obstacles to the implementation of the safety of employees mills in PT. Perkebunan Nusantara V Sei Garo is the lack of human resources, lack of personal protective equipment, work locations that are less clean and a lack of understanding and awareness of the employees themselves. Third, efforts to do that is to provide competent human resources, provide personal protective equipment, maintain the cleanliness of the work site and provide extra fooding.Keywords: Implementation - Safety and Health - Employee